1972
DOI: 10.2475/ajs.272.5.438
|View full text |Cite
|
Sign up to set email alerts
|

The viscosity of magmatic silicate liquids; a model calculation

Abstract: INTRODUCTIONThere are very few aspects of igneous petrology which are not in some way closely related to the viscosity of magma. Rate of crystal growth, gravitative settling or rise of solids and bubbles, mode of volcanic eruption, flow differentiation mechanisms, flow characteristics of lavas, mass transfer in magmas under externally imposed pressure gradients or natural convection, rate of cooling of magmatic intrusions and lavas; all of these phenomena are critically dependent upon the viscosity of magmatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
257
1
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 700 publications
(276 citation statements)
references
References 21 publications
9
257
1
1
Order By: Relevance
“…The convective velocity (from the mixing length formula (equation (10)) with a heat flux of 150 W/m 2 ) of the magma ocean will be approximately 10 cm/s. We estimate that the viscosity of crystal-free magma will be =1 P [Bottinga and Weill, 1972]. With these assumptions, a crystal radius of 2:3.5 em (equation (12b)) is required for crystal flotation/settling to occur in the absence of a boundary layer.…”
Section: Crystal-liquid Fractionation In the Depth Range Of The Uppermentioning
confidence: 99%
See 1 more Smart Citation
“…The convective velocity (from the mixing length formula (equation (10)) with a heat flux of 150 W/m 2 ) of the magma ocean will be approximately 10 cm/s. We estimate that the viscosity of crystal-free magma will be =1 P [Bottinga and Weill, 1972]. With these assumptions, a crystal radius of 2:3.5 em (equation (12b)) is required for crystal flotation/settling to occur in the absence of a boundary layer.…”
Section: Crystal-liquid Fractionation In the Depth Range Of The Uppermentioning
confidence: 99%
“…We estimate the crystal size by evaluating each of these equations, determining the Reynolds number for each case, and selecting the result that is consistent with the Re conditions. For perovskite in the lower mantle, the maximum crystal-liquid density contrast will be ::0.25 g/cm 3 ‱ If the viscosity of molten Cl obeys an Arrhenius relationship, independent of pressure, then we would estimate a lower limit for the viscosity to be :: 0.01 P [Bottinga and Weill, 1972]. The combined pressure and temperature dependence of viscosity is unknown for silicate liquids under these conditions so this value for viscosity must be suspect.…”
Section: ]mentioning
confidence: 99%
“…Hence, the evolution of viscometers for silicate liquids has been traced by changing from Arrhenian temperature dependence (e.g. Shaw 1972;Bottinga & Weill 1972) to non-Arrhenian models, considering magma composition and volatile effects (e.g. Baker 1996;Hess & Dingwell 1996;Russell et al 2002;Giordano & Dingwell 2003;Russell & Giordano 2005;Giordano et al 2006;Vetere et al 2006;Hui & Zhang 2007;Giordano et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A complete understanding of magma rheology requires a comprehensive description of the rheology of the melt phase [Shaw, 1965], Most studies of shear viscosities of Silicate melts have been conducted at conditions of relatively high temperatures and low viscosities (see compilations by Bottinga and Weill [1972], Bansal and Doremus [1986], and Ryan and Blevins [1987]). In cases where the stress-strain rate relationship has been investigated over a significant rĂ€nge of strain rate, both Newtonian behavior (i.e., linear stress-strain rate relationship) [e.g., Scarfe et al, 1983] and non-Newtonian behavior [e.g., Li and Vhlmann, 1970;Simmons et al, 1982;Spera et al, 1982] have been observed.…”
Section: Introductionmentioning
confidence: 99%